Family carers' experiences of receiving the news of a diagnosis of Motor Neurone Disease: A national survey - Aoun, Samar; Breen, Lauren; Oliver, D.; Henderson, R.; Edis, R.; O'Connor, M.; Howting, D.; Harris, R.; Birks, C. (Elsevier, 2017)
Family carers have a central role in the care and support of people with MND and face the challenges of the disease from diagnosis to progression and the multiple losses of MND, but their support needs are often neglected. This study aimed to investigate the experiences of family carers at the time of diagnosis and their satisfaction with receiving the news. An anonymous postal survey was facilitated by all MND Associations in Australia (2014) and 190 family carers completed the questionnaire. The questions centred on the SPIKES protocol for communicating bad news. Two-thirds of family carers rated the skills of their neurologists as above average and were satisfied with the delivery of the diagnosis, in terms of having a significantly longer consultation time, the neurologist being warm and caring, satisfaction with the amount and content of information they received and relevant supports, and a plan for following up support. Conversely those who rated the neurologist's skills as below average commented on the difficulties they encountered and the long term emotional stress engendered by poor communication. The study emphasises previous research that suggested that neurologists may require education and training in communicating the diagnosis and this should include family carers as a vital member in MND care.